2018
DOI: 10.1007/s00216-018-1286-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of thermally labile pesticides by on-column injection gas chromatography in fruit and vegetables

Abstract: Thermally labile pesticides (captafol, captan, dicofol, and folpet) are highly prone to suffer thermal degradation during sample introduction into a gas chromatograph (GC) to tetrahydrophthalimide (THPI), 4,4'-dichlorobenzophenone (DCBP), and phthalimide (PI), respectively, mainly produced in the glass liner of the injector. This undesired behavior leads to inaccurate qualitative and quantitative results. Direct on-column injection (OCI) technique is evaluated as an alternative to avoid or minimize compound al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…This adsorbent, a primary and secondary amine, can interact with acidic compounds yielding low recoveries after the clean-up step. Folpet is widely reported as a troublesome compound for GC–MS analysis because of its thermal degradation [6]. Moreover, it is reported that chlorothalonil presents recovery problems in some matrices when extracted with acetonitrile.…”
Section: Methods Detailsmentioning
confidence: 99%
“…This adsorbent, a primary and secondary amine, can interact with acidic compounds yielding low recoveries after the clean-up step. Folpet is widely reported as a troublesome compound for GC–MS analysis because of its thermal degradation [6]. Moreover, it is reported that chlorothalonil presents recovery problems in some matrices when extracted with acetonitrile.…”
Section: Methods Detailsmentioning
confidence: 99%
“…At present, PPO-inhibiting herbicides mainly include diphenyl ethers, phenylpyrazoles, triazolinones, N -phenyl phthalimides, and diazoles [ 39 ]. Among these herbicides, diphenyl ethers (DPEs) [ 40 ] had been widely studied by researchers in the creation of novel pesticides due to their high efficiency, low toxicity, high selectivity, and simple synthesis process; Ye Fei’s team committed to the research and development of PPO inhibitors for a long time. Several series of compounds ( Figure 4 ) containing phenoxypyridine had been designed, studied for greenhouse herbicidal activity, PPO inhibitory activity, crop selectivity, and structure-activity relationships (SARs).…”
Section: Herbicides Containing Phenoxypyridine Scaffoldmentioning
confidence: 99%
“…On the one hand, substructure splicing is a widely used method for inventing novel drugs. The use of substructure splicing or parallel synthesis to optimize specific structures has led to a number of potential lead compounds and achieved great success in discovering new drug candidates. On the other hand, tetrahydrophthalimide herbicides have many advantages, such as strong selectivity and no phytotoxicity to crops. , In addition, N -phenyl-phthalimide herbicide as another type of PPO inhibitor also has advantages of short residual time, fast degradation rate, and no pollution to the environment. For example, Flumioxazin has a degradation half-life of only 10.6–32.1 days in the field site at 15 and 25 °C and its degradation pathway is mainly through the opening of the imide ring, followed by the cleavage of the amide bond to form the corresponding dicarboxylic acid and aniline .…”
Section: Introductionmentioning
confidence: 99%